(3HZjI GdWGdH aj eYQaI GdeaQhV hGdhGLHs - (3GdMdj, GdLfGLj, GdfLaj, ef Bd cGTa GdZWGA, LYaQ Hf NVQ Hf TdGd, J (B1227 (3g`s ((3eMeO Ydj Hf SjO UGdM GdMcjes)
(3ChdgG (B:s
(3GdMeO ddg GdPj CSS bhGYO GdCMcGe(B...(3hHYO abO SCdfj LeY ef GdCJbjGA(B...(3Cf CcJH dge QSGdI eMJhjI Ydi CUhd GdhGLHGJ(B...s
(3BNQgG (B:s
(3GUWMHG aj GdChdJjf hGaJQbG aj GdCNjQJjf hjSJMH GdLHQ YbjH cd ebUhQI Ydi GSJMHGHg HYO cd aQjVI(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B2(3,U(B124s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B491s
(3GdPQjYI(B:(3L(B3(3,U(B74(3,Qbe(B451s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3CUhd Gdabgs